2021
DOI: 10.3390/vaccines9111238
|View full text |Cite
|
Sign up to set email alerts
|

Natural Flt3Lg-Based Chimeric Antigen Receptor (Flt3-CAR) T Cells Successfully Target Flt3 on AML Cell Lines

Abstract: Relapsed/refractory acute myeloid leukemia (AML) cannot be cured with chemotherapy alone, as the blasts survive the treatment. Chimeric antigen receptor (CAR) approaches for AML are being actively developed. CARs promote immune reactions through recognition of the target molecular epitopes at the surface of cancer cells. The recognition involves the extracellular portion of the CAR protein, which corresponds to either the antibody or the physiological binding partner of the targeted antigen. Here, we design a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Multiple inhibitors of FLT3 are FDA approved for use in FLT3 + AML including gilteritinib, midosaurin, and quizartinib, so it is not surprising that FLT3 CARs are being investigated. Currently all published work is preclinical, but has showed promising activity against leukemic cell lines [114][115][116][117][118]. Many groups are using safety switches to allow for bone marrow recovery afterwards, given that FLT3 also depleted HSCs [38].…”
Section: Flt3mentioning
confidence: 99%
“…Multiple inhibitors of FLT3 are FDA approved for use in FLT3 + AML including gilteritinib, midosaurin, and quizartinib, so it is not surprising that FLT3 CARs are being investigated. Currently all published work is preclinical, but has showed promising activity against leukemic cell lines [114][115][116][117][118]. Many groups are using safety switches to allow for bone marrow recovery afterwards, given that FLT3 also depleted HSCs [38].…”
Section: Flt3mentioning
confidence: 99%
“…The CARs were encoded on a bicistronic lentiviral vector using the same promoter and separated by a self-cleaving 2A peptide to ensure equal expression on the cell surface [ 35 ]. ( E ) A third generation anti-FLT3 CAR with two co-stimulatory domains, 4-1BB and inducible T-cell co-stimulator (ICOS) [ 36 ].…”
Section: Configuration Of Chimeric Antigen Receptorsmentioning
confidence: 99%
“…While most studies used an scFv derived from known antibodies, Sommer et al developed and screened their own scFvs from a phage-display library [ 33 ]. In contrast to using scFvs, Wang et al and Maiorova et al targeted FLT3 using its natural ligand, FLT3 ligand (FLT3L) [ 34 , 36 ]. This has the advantage of potentially eliminating problems with immunogenicity, and the natural ligand might display higher specificity than scFvs.…”
Section: In Vitro Assessment Of Efficacy and Safety Of Anti-flt3 Car ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, treatment with CAR T cells did not inhibit hematopoietic cell colony formation when cultured with CD34+ healthy human umbilical cord blood stem cells despite FLT3 expression in hematopoietic stem cells (HSCs) [ 122 ], indicating little off-target toxicity in the hematopoietic compartment, at least in vitro. Maiorova et al [ 93 ] also developed a ligand-based CAR targeting FLT3 utilizing the full-length FLT3L. The authors found the enhanced killing of FLT3+ THP-1 cell lines by CAR T cells in vitro, though in vivo studies are still needed to determine efficaciousness.…”
Section: Natural Receptor- and Ligand-based Car T Cell Therapies In Preclinical Studiesmentioning
confidence: 99%